AKTIFITAS BERBAGAI SEDIAAN BUAH SIRSAK (Annona muricata Linn) DALAM PENURUNAN KADAR ASAM URAT TIKUS PUTIH Sprague-Dawley - - Prasetyorini; - Moerfiah; Sri Wardatun; - Affandi (Universitas Pakuan, 2014)
Research potential of juice, extract ethanol, ethyl acetate extracts with different doses of soursop fruit as down as the asamurat has been performed. The treatment given these supplies juice with doses of 930 mg, 1870 2810 mg and mg: 96% ethanol extract with a dose of 26.79 g/100 ml, 53.58 g/100 ml and 80.37 g/100 ml; and extract with ethyl acetate dose 2.58 g/100 ml, 5.16 g/100 ml and 7.74 g/100 ml. The making of extracts is done with methods of maceration of fruit juice, and squeeze the flesh of the fruit directly with Batiste. The results of qualitative testing all positive preparations contain a flavanoid, alkaloids, tannins, saponins and polyphenols. The content of polyphenols 100 g ingredients for fruit juice, extract 96% ethanol and ethyl acetate extracts of consecutive 0.473 g SAG: SAG 0.324 g; and 0.194 mg SAG. Vitamin C 100 g of ingredients for fruit juice, extract 96% ethanol and ethyl acetate extracts of consecutive 38.24 mg; 30.56 mg; 35.66 mg. for 100 g K Content material to juice, extract the ethanol 96% ethyl acetate extracts and a row of 0.39 g; 0.26 g; 0.22 g. Content of 100 g each Na ingredients for fruit juice, extract the ethanol 96% ethyl acetate extracts and a row of 0.0269 g; 0.0416 g; 0.0436 g. The results showed the treatment given the very real effect of lowering uric acid levels of rats, a third dose of juice lowers blood uric acid levels up to 40%, 96% ethanol extract Dosage dose 53.58 g/100 ml and 80.37 g/100mlserta ethyl acetate extract dosage 7.74 g/100 ml can also lower blood uric acid levels exceed the positive control.Key words: Uric acid, fruit juice, ethanol and ethyl acetate extract fruit soursop (Annona muricata Linn),